(3QSGdI aj GdHGgs - (3GdMSjf Hf YHO Gddg Hf GdMSf Hf Ydj Hf SjfG , CHh Ydj GdnHrdNqj Ke GdoHNGQqj GdeYQha HGHf SjfG, (B427 (3g`s
(3ChdgG (B:s
(3eSCdI WHjI SFd YfgG GdTjN GdQFjS CYdi Gddg OQLGJg HehLHgG SCd YfgG HYV GdCcGHQ s
(3BNQgG (B:s
(3RjGOI ajeG bdHJ , SGQYJ Edi GdRjGOI Ef TGA Gddg JYGdi s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B241s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdChd (B- (3U (B30 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdeJMa GdHQjWGfi (B(add 23403) s
Keywords: (3GdWHs